Relationship Between Protein Source Eating Habits and Sleep Duration with the Incidence of Anemia in Female Adolescents in Grade VII Study at SMPN 1 Kelumpang Hilir UPTD Puskesmas Serongga - Suryani Suryani; Rusmini Yanti; Rahmani Rahmani; Yasir Farhat (SEAN Institute, 2026)
Anemia is one of the most common nutritional problems among adolescent girls, especially during periods of rapid growth. One of the main factors causing anemia is low intake of animal protein, which contains haem iron and plays an important role in hemoglobin formation. Adolescent girls have higher iron requirements, so they are at greater risk of anemia if their diet is insufficient. 49.7% of adolescent girls experience anemia. The anemia problem at SMPN 1 Kelumpang Hilir is 27.6%. This study used an analytical observational research design with a cross-sectional approach. The population in this study consisted of 171 female adolescents from SMP Negeri 1 Kelumpang Selatan. The study was conducted in November 2025. The sampling technique used was purposive sampling. The test used was the Spearman's rank correlation test. The results of the study showed that most of the adolescent girls had poor protein intake habits (60.0%), insufficient sleep duration (58.6%), and anemia (70.0%). The statistical test results showed a relationship between protein source eating habits and sleep duration with the incidence of anemia in female adolescents in grade VII at SMPN 1 Kelumpang Hilir UPTD Puskesmas Serongga. It is recommended that there be education on the proper consumption of TTD (avoiding tea/coffee) as well as improvements in protein intake and sleep patterns among adolescent girls. Researchers are further recommended to examine the variables of social support and knowledge levels.